Fresnel's diffraction and scintillation of gravitational waves - Vetrugno, D; Congedo, G; De Paolis, F; Longo, P; Nucita, A; Qadir, A (2007)
Diffraction effects on gravitational waves propagating through a stellar cluster are analyzed both in the Fraunhoffer and Fresnel approximations. It is also found that a gravitational wave scintillation effect comes out naturally, implying that the gravitational wave intensity changes in a characteristic way as the observer moves. © Società Italiana di Fisica.